1972
DOI: 10.1172/jci107145
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Lipoproteins, Bile Acids, and Red Cell Membranes Associated with Target Cells and Spur Cells in Patients with Liver Disease

Abstract: A B S T R A C T MNlost p)atiellts witlh stable cirrhosis of the alcoholic have "target" red cells; however, a minoritv have "spur" cells and severe hemolytic anemia. These two syndromes were studied in 27 patients with target cells and 17 patients with spur cells, all of whom had advanced cirrhosis. The cholesterol and phospholipi(d content of red cell membranes effectively distinguished target cells from spur cells. Target cells alone were rich in lecithin, and both the cholesterol/phospholipid and cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(83 citation statements)
references
References 56 publications
5
78
0
Order By: Relevance
“…Bile acids are amphipathic and are capable of insertion into the lipid-water interphase as has been suggested for erythrocytes (29)(30)(31), thus resulting in altered membrane permeability to water, inorganic anions, and inert molecules such as inulin. Scanning electron microscopic studies from our laboratory demonstrated irregularities and outpouchings in the canalicular surface membranes Bile Flow (ml/24h) 300 FIGURE 8 Predicted differences in the diffusion permeability constant (K) during administration of7.0 ,umol/min taurocholic acid followed by 3.5 ,umol/min (solid lines) and 3.5 umol/min taurocholic acid followed by 7 of rats infused with bile acids, alterations which might occur through such a bile acid-canalicular membrane interaction and account for some of the differences in choleretic effect which we observed.…”
Section: Discussionmentioning
confidence: 95%
“…Bile acids are amphipathic and are capable of insertion into the lipid-water interphase as has been suggested for erythrocytes (29)(30)(31), thus resulting in altered membrane permeability to water, inorganic anions, and inert molecules such as inulin. Scanning electron microscopic studies from our laboratory demonstrated irregularities and outpouchings in the canalicular surface membranes Bile Flow (ml/24h) 300 FIGURE 8 Predicted differences in the diffusion permeability constant (K) during administration of7.0 ,umol/min taurocholic acid followed by 3.5 ,umol/min (solid lines) and 3.5 umol/min taurocholic acid followed by 7 of rats infused with bile acids, alterations which might occur through such a bile acid-canalicular membrane interaction and account for some of the differences in choleretic effect which we observed.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the protein can be useful to modify normal erythrocytes so as to mimic abnormal red cells, which are often acquired in patients with a liver disease. These hemolytic syndromes are associated with a disordered plasma lipoprotein metabolism, inducing red cell modifications [29][30][31][32][33][34][35][36]. 'Spur' cells are such abnormal erythrocytes, which are characterized by an increased content of cholesterol and PC, be it that the total amount of phospholipids is comparable to that in normal erythrocytes [23,29,33,36].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated amounts of PC and cholesterol are also found in the so-called 'target' cells. These red cells are characterized by their targeted appearance, due to an increased surface area induced by an elevated lipid content [29,31,33,35]. The amount of cholesterol may range between 25% and 75% above normal in these cells, whereas the enhancement in phospholipid content is approx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated an increase in membrane lipid in normal red cells (which formed target cells) and in HS red cells (which became less spheroidal) in a bile salt environment in vitro and in patients with obstructive jaundice resulting in a decrease in osmotic fragility, perhaps enabling these red cells to survive longer in the splenic circulation (Cooper & Jandl, 1969a,b). Cooper also provided the first clear explanation of the lipid abnormalities leading to red cell defects in spur cells and target cells in patients with severe chronic liver disease (Cooper, 1969;Cooper et al, 1972). Aster and Jandl (1964) refined methods using Cr 51 -labelled platelets, and showed the survival and sequestration of platelets in normal subjects, in those with splenomegaly (where the splenic pool may harbour 50-90% of platelets) (Aster, 1966) and in patients with autoimmune thrombocytopenia (Aster & Keene, 1969).…”
Section: Red Cell Shapesmentioning
confidence: 99%